P316 A study on the impact of diagnosis on the level of exercise amongst patients with IBD. (16th January 2018) - Schembri, J; Gatt, K; Katsanos, K H; Christodoulou, D K; Balomenos, D; Karmiris, K; Pontas, C; Kopylov, U; Koutroubakis, I; Foteinogiannopoulou, K; Fábián, A; Molnár, T; et al.
Abstract: Background: IBD can impair the functional capacity of patients who may find it discouraging to maintain their level of fitness after diagnosis. Nevertheless, IBD patients perceive exercise and sports as being helpful in managing their psychological health and reducing some of the symptoms and complications of IBD. Our aim was to determine the impact of IBD diagnosis on fitness levels. Methods: We conducted a prospective, multi-centre, cross-sectional survey study where patients with a confirmed diagnosis of IBD within the previous 18 months were recruited. Patients who had not been in clinical remission and/or had had treatment changes within the previous 6 months were excluded. Clinical data were collected from medical databases and surveys were administered in order to estimate levels of exercise before and after diagnosis by means of Godin scores. Severe disease was defined as need for surgery and/or anti-TNF-alpha medications. Results: A total of 158 patients (100 Crohn's disease; 58 ulcerative colitis) from 7 different European centres were recruited. Mean age was 35.1 years (95% CI ± 2.0) and gender distribution was approximately equal (51.3% male). The mean Harvey–Bradshaw and simple clinical colitis activity indices were 2.25 (95% CI ± 0.40) and 1.64 (95% CI ± 0.49) respectively. Mean Godin score difference before and after IBD diagnosis was 6.94 (95% CI ± 4.28, p = 0.002). Mean premorbid Godin scores were significantly higher (ANOVA p = 0.001) amongst patients who experienced a reduction in activity (39.5, 95% CI ± 6.3) compared with those who experienced either no change (26.9, 95% CI ± 5.3) or even an improvement in their level of exercise (12.1, 95% CI ± 3.8) after diagnosis. Mean BMI was slightly higher after diagnosis however this did not reach statistical significance ( p = 0.072) and was still within the normal range (24.98 kg m −2 ). Patients with UC (41.8%) were more likely than patients with CD (23%) to reduce their level exercise (χ 2 p = 0.04). However, there was no significant association for the diseases between reduction in exercise and disease severity and/or frequency of relapses. Conclusions: Patients were significantly less physically active after a diagnosis of IBD and this was more apparent in UC. Furthermore, individuals with a high premorbid level of physical activity seem to be affected most. A higher BMI after diagnosis could be attributable to this reduction in exercise levels but also to better disease control. Prompt identification of risk factors associated with loss of fitness levels would help address the reduced quality of life that may be associated with lack of physical activity.